2013
DOI: 10.1097/qad.0b013e32836010dd
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D attenuates nucleoside reverse transcriptase inhibitor induced human skeletal muscle mitochondria DNA depletion

Abstract: Objective To evaluate the impact of the active metabolite of vitamin D, 1α,25-dihydroxycholecalciferol (1,25D3), on nucleoside reverse transcriptase inhibitor (NRTI) induced mitochondrial DNA (mtDNA) depletion in human skeletal muscle myoblasts and myotubes. Design mtDNA was quantified in human skeletal muscle myoblasts and myotubes following 1,25D3 and NRTI treatment using real-time PCR. Methods Human skeletal muscle myoblasts and myotubes were treated with didanosine (ddI), stavudine (d4T), zidovudine (Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Quan et al [99] demonstrated that oral BPA exposure in dams (gestational days (GD)) [14][15][16][17][18][19][20][21] provokes an increased ROS production, the activation of the apoptotic pathway in the testis of male offspring, confirmed by histopathological changes. BPA exposure in CD-1 dams (GD 7-14) also led to the alteration of sperm quality and motility in adult male mice, with changes in oxidative balance [100]. Furthermore, in a murine model of chronic BPA exposure of dams, during all gestational period, and continuing the oral administration to male pups until to sexual maturation, damaged spermatogenesis was observed in progenies [101].…”
Section: Oxidative Stress-induced Bpa Toxicity On Male and Female Rep...mentioning
confidence: 99%
“…Quan et al [99] demonstrated that oral BPA exposure in dams (gestational days (GD)) [14][15][16][17][18][19][20][21] provokes an increased ROS production, the activation of the apoptotic pathway in the testis of male offspring, confirmed by histopathological changes. BPA exposure in CD-1 dams (GD 7-14) also led to the alteration of sperm quality and motility in adult male mice, with changes in oxidative balance [100]. Furthermore, in a murine model of chronic BPA exposure of dams, during all gestational period, and continuing the oral administration to male pups until to sexual maturation, damaged spermatogenesis was observed in progenies [101].…”
Section: Oxidative Stress-induced Bpa Toxicity On Male and Female Rep...mentioning
confidence: 99%
“…The third method is to use a ranging sensor to describe the motion by distance. The extraction of data on bone and the joint center has become a research hotspot [ 10 ]. The extraction of human bones and joint centers based on point cloud data is processed by processing the point cloud data of the real human body acquired by the three-dimensional scanner, thereby extracting semantic information such as the skeleton and joint center of the human body model [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, although the exact significance of the cells´ death in the development of the disease is still uncertain, the manipulation of cell death pathways will eventually affect the course of the infection [ 11 , 15 ]. Although the interplay between the mononuclear phagocytes-apoptosis and the mycobacterial control is still under investigation, there is evidence that apoptosis pathways are able to trigger inflammatory mediators (pyroptosis) and autophagy which may serve to limit bacterial intracellular growth [ 16 – 19 ].…”
Section: Introductionmentioning
confidence: 99%